An Experientially Derived Model of Flexible and Intentional Actions for Weight Loss Maintenance After Severe Obesity - Natvik, Eli; Råheim, Målfrid; Andersen, John Roger; Moltu, Christian (Frontiers in Psychology, 2019)
Background: Knowledge about nonsurgical weight loss (WL) is scarce among people with severe obesity (SO). Lifestyle changes are primarily self-driven, occasionally accompanied by professional guidance and weight-management support. Weight regain and intervention discontinuation are common challenges among guidance and support programmes. In the current study, we describe a model of meaningful strategies for maintaining WL after SO based on the experiences of successful cases. Methods: Aiming to investigate the experiences of WL and WL maintenance (≥ five years) following SO, we designed a qualitative study. Ten adults (eight women and two men) participated in individual in-depth interviews. The interviews concentrated on participants’ experiences of losing weight and maintaining a lower weight over the long term. The transcripts were analysed with a rigorous method for thematic cross-case analysis, namely, systematic text condensation (STC). Results: Participants identified four experiential themes at the core of long-term weight loss maintenance: (a) Owning the decision, (b) Creating self-reinforcement, (c) Sustaining a lifestyle-forming identity, and (d) Selecting support appropriate to one’s own situation. These core themes represent the intentional level, functioning both as the foundation of and the momentum for sustaining weight loss. On the behavioural level, participants continued to take action for change, obtain results, record and reflect on their efforts and milestones, observe what worked and felt good, and receive recognition from others, thereby realizing changes. Conclusions: Based on these results, we propose a model of weight loss maintenance after SO, suggesting that practices towards WL maintenance on the behavioural level achieve meaning and sustainability through their relationship with a core intentional level found across participants’ experiences. One implication is that the relationship between the intentional and behavioural levels might be more meaningful when discussing long-term weight loss maintenance than the behaviours themselves.